2013
DOI: 10.5301/ijao.5000178
|View full text |Cite
|
Sign up to set email alerts
|

A New Gyro-Based Method for Quantifying Eyelid Motion

Abstract: The new gyro-based method proved to be a valuable tool to provide dynamic and real-time quantification of eyelid motions. It could be particularly useful for evaluating the effective and natural-like eyeblink restoration provided by ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In closed-loop methods, the system detects eye blink -related signals from the healthy side of the face in order to trigger concurrent blink on the paralyzed side eye. The measurement methods include, for example, electromyography (EMG), electrooculography (EOG), and the use of infrared (IR) emitter-sensor pair or gyroscopic sensor in detecting eye closure [3,4,5,6]. Previous studies have shown that stimulation of the orbicularis oculi muscle and/or facial nerve branches using transcutaneous electrodes can be useful in restoring eye blink in about 50% of the cases [7].…”
Section: A Facial Pacing Methodsmentioning
confidence: 99%
“…In closed-loop methods, the system detects eye blink -related signals from the healthy side of the face in order to trigger concurrent blink on the paralyzed side eye. The measurement methods include, for example, electromyography (EMG), electrooculography (EOG), and the use of infrared (IR) emitter-sensor pair or gyroscopic sensor in detecting eye closure [3,4,5,6]. Previous studies have shown that stimulation of the orbicularis oculi muscle and/or facial nerve branches using transcutaneous electrodes can be useful in restoring eye blink in about 50% of the cases [7].…”
Section: A Facial Pacing Methodsmentioning
confidence: 99%
“…The most frequently proposed method for non-invasively detecting blink on the intact side is through skin surface electromyographic (EMG) recording of the orbicularis oculi muscle 47 , followed by detection of periocular tissue movements through gyroscopes 8 or accelerometers. 9 Although these approaches demonstrate promise for accurately detecting blinks, they require placement of sensors on the face surface, which complicates device use and potentially influences dynamics of healthy blinks.…”
Section: Introductionmentioning
confidence: 99%
“…A measure of 0.3% of American and Western European people suffer from facial nerve palsy (FNP) every year [ 1 , 2 ]. FNP and Bell palsy can lead to ptosis, and consequently, loss of eyelid movement, blinking disruption, and corneal damage.…”
Section: Introductionmentioning
confidence: 99%